PURE ELECTRON PLASMA STRUCTURES FORMATION IN AN EXTERNAL CONSTANT MAGNETIC FIELD - Moskvitina, Yuliya K.; Tkachenko, Ivan V. (East European Journal of Physics, 2014)
Behavior of the pure electron plasma column rotating in an external constant magnetic field described in the kinetic approach is investigated. The initial stage of the axially asymmetric electrostatic oscillations instability development is considered. It is shown that the exponential increase of the electrostatic potential leads to the redistribution of the beam’s density due to the ponderomotive force existence. The electrons motion under the influence of ponderomotive forces is modeled numerically. The simulation results are presented graphically in the form of particles set distribution in the beam’s cross section. Qualitative estimates of the beam coupling parameter, which indicates the possibility of electron plasma cooling process are submitted.